THE EFFECT OF SORGHUM AND COWBEAN DRYING TEMPERATURE ON THE PHYSICOCHEMICAL AND SENSORY PROPERTIES OF CEREAL DRINK POWDER - Ramanda, Muhammad Rizky; Ulfa, Masayu Nur; Rahma, Zarlita Dwi (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2026)
Chronic Energy Deficiency (CED) is a condition that occurs due to an imbalance between energy and protein intake, so that the body's nutritional needs are not optimally met. Government efforts to prevent CED and KEP (Energy Protein Deficiency) are carried out through the Supplementary Feeding (PMT) program, which aims to improve the nutritional status of pregnant women and toddlers. Sorghum (Sorghum bicolor (L.) Moench) is a cereal commodity that has the potential as an alternative to wheat. Meanwhile, cowpea (Vigna unguiculata) is a local bean that has high nutritional value, especially as a source of vegetable protein. This study aims to evaluate the effect of variations in sorghum and cowpea drying temperatures on the physicochemical and sensory characteristics of cereal drink powder. Tests conducted include physical analysis (ash content, water content, solubility, viscosity, and rehydration time) and sensory testing through hedonic tests. The results showed that variations in drying temperature at 50oC, 60oC, and 70oC significantly affected the viscosity value at speeds of 6 rpm, 12 rpm, 30 rpm, and 60 rpm with a range of 41.87–68.65 mPas, and significantly affected the color parameter (b*) with a range of 10.98–12.75. In the hedonic test, temperature treatment also showed a significant effect on taste parameters and overall acceptance. However, there was no significant effect on ash content, water content, solubility, rehydration time, or hygroscopicity rate. Keywords: Cereal drink powder, cowpea, physicochemical, sorghum.